Trust Through Data: Managing Risk in the Digital Age - Kunšek, Mojca; Miklič, Barbara; Tekavči, Metka (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2025)
Risks reflect the uncertainty and exposure to which a business entity is subject. They may stem from global factors, as well as business risks related to the stability of business partners and internal vulnerabilities, such as cyber risks. Research shows that almost 5% of annual revenue is lost worldwide each year due to fraud. Our research focused on managing external factors that contribute to fraud. The main objective of this paper is to analyse the impact of digitalisation on stable business and sustainable entrepreneurship. Methodologically, the research approach partly relies on the Global Entrepreneurship Monitor (GEM) and results of a survey on the use of official data in verifying business partners among small and medium entrepreneurs (SME). The key findings revealed clear recommendations from experts in the GEM survey, as well as business experts, emphasising the need to incorporate relevant, digitally and sustainably oriented topics into all educational programs and business practices.
Keywords: GEM; AI adoption; Fraud prevention; AJPES; Data; Sustainability